Penerapan Model Visualization Auditory Kinesthetic (VAK) dengan teknik probing prompting untuk meningkatkan kemampuan pemahaman konsep matematis dan keaktifan belajar siswa SMP pada materi segiempat dan segitiga - Indriani, Indriani; El Hakim, Lukman; Hidajat, Flavia Aurelia (UNIVERSITAS NEGERI MALANG, 2023)
This study aims to improve the ability to understanding mathematical concepts and student learning activities through the application of the Visualization Auditory Kinesthetic model with the Probing Prompting technique. This type of research is Classroom Action Research which consists of three cycles based on the Kemmis and McTaggart models. There were 6 students who were research subjects in this study representing students with high, medium and low. Data analysis techniques use the stages according to Miles and Huberman, including data reduction, data presentation and conclusions. The results showed that learning mathematics by applying the VAK model with the Probing Prompting technique could improve the ability to understand mathematical concepts and student learning activities. The increase in the ability to understanding mathematical concepts can be seen from the increase in the average score of the test results in each cycle with the average score in the first cycle is 50, the average score in the second cycle is 65, and the average score in the third cycle is 79. As for the score learning activity also increased starting from the average in the first cycle is 68, the average in the second cycle is 76, and the average in the second cycle is 77.